Sustainable Mitigation of Methane Emission by Natural Processes - Yucheng, Cao; Cel, Wojciech (Problemy Ekorozwoju, 2015)
It has been observed that employing the natural processes occurring in the Earth’s ecosystem for mitigating the greenhouse gases emission is sustainable. One of the main sources of methane emission is agriculture (rice cultivation and livestock raising). Limiting the cultivation of rice would not be sustainable, as it is the basic source of alimentation for a large share of human population. On the other hand, introducing feed additives which limit the methane production in rumens can be considered sustainable. Another significant source of methane emission are landfills. Utilizing this gas for energy purposes is the most sustainable solution. However, as only part of methane can be used as the source of energy, the natural process of methane oxidation by methanotrophic bacteria occurring in soil may contribute to sustainable reduction of its emissions from landfills.